The term structure of interest rates and economic activity in South Africa - Shelile, Teboho (Rhodes University, Faculty of Commerce, Department of Economics, 2007)
Many research papers have documented the positive relationship between the slope of the yield curve and future real economic activity in different countries and different time periods. One explanation of this link is based on monetary policy. The forecasting ability of the term spread on economic growth is based on the fact that interest rates reflect the expectations of investors about the future economic situation when deciding about their plans for consumption and investment. This thesis examined the predictive ability of the term structure of interest rates on economic activity, and the effects of different monetary policy regimes on the predictive ability of the term spread. The South African experience offers a unique opportunity to examine this issue, as the country has experienced numerous monetary policy frameworks since the 1970s. The study employed the Generalised Method Moments technique, since it is considered to be more efficient than Ordinary Least Squares. Results presented in this thesis established that the term structure successfully predicted real economic activity during the entire research period with the exception of the last sub-period (2000-2004) when using the multivariate model. In the periods of financial market liberalisation and interest rates deregulation the term structure was found to be a better predictor of economic activity in South Africa. These findings emphasise the importance of considering the prevailing economic environment in testing the term structure theory.
Keywords: Finance -- South Africa; Monetary policy -- South Africa; Interest rates -- South Africa; Economic development -- South Africa; South Africa -- Economic conditions -- 21st century